PENGARUH LIKUIDITAS, LEVERAGE, KOMISARIS INDEPENDEN, MANAJEMEN LABA,DAN KEPEMILIKAN INSTITUSIONAL TERHADAP AGRESIVITAS PAJAK PERUSAHAAN (Studi pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia periode 2011-2013) - Fadli, Imam; Ratnawati, Vince; Kurnia, Pipin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to examine and analyze the effect of liquidity, leverage, independent commissioner, earnings management, and ownership institusional against the aggressiveness of corporate tax.The method used in this research is descriptive method. The population in this study is a company listed on the Indonesia Stock Exchange. The sampling technique using purposive sampling method prescribed researchers for years 2011 to 2013. The sample was manufacturing companies listed in Indonesia Stock Exchange (BEI). Hypothesis testing transactions are carried out using multiple linear regression approach. The statistical test equipment used is a program Statistical Product and Service Solutions (SPSS). Data used in the form of corporate financial statements contained in ICMD and http://www.idx.co.id/ website. Results from this study indicate that the independent commissioner liquidity and significant negative effect, with a significance of liquidity (0.025 <0.05) and independent commissioners (0.011 <0.05). Leverage and significant positive effect on earnings management, with a significance value of leverage (0.017 <0.05) and earnings management (0.038 <0.05) as well as institutional ownership (0.082> 0.05), which does not affect the aggressiveness of corporate tax.Keywords: Liquidity, Leverage, Independent Commissioner, Earnings Management, and Aggressiveness Taxes.